The Methods of Training Young Military Pilots - A. Khamraev (Zien Journals, 2022)
This article analyzes strategic issues in Air Force undergraduate pilot training (SUPT). Also it describes the key variables that determined pilot training’s historical development, what type of training system, generalized or specialized, produces the best cost to effect. Furthermore, it evaluates recent structural changes to SUPT and analyzes the pilot training systems of the Air Force of Uzbekistan. It synthesizes the study’s findings and implications to suggest an optimal course for future Air Force pilot training.
Keywords: methods; young pilot; military pilot; specialized undergraduate pilot training